2019
DOI: 10.1136/bmjopen-2018-023742
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a specific training programme on the neuromodulation of pain in female patient with fibromyalgia (DouFiSport): a 24-month, controlled, randomised, double-blind protocol

Abstract: IntroductionThe main symptom of fibromyalgia (FM) is diffuse pain. There is currently no aetiological treatment for FM. However, all pain associations and best practice guidelines strongly advocate the practice of aerobic physical activity to improve the symptoms of FM subjects. The mechanisms of dysfunctional pain are mostly central and related to stress axis dysfunction (autonomic nervous system and corticotropic axis). Our main objective is to assess the efficacy of a specific training programme on endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
6
0
1
Order By: Relevance
“…In the studies that were analysed, significant values were found for at least one of the evaluated parameters in all studies: (i) physical fitness tests [ 1 , 23 , 33 , 36 , 37 , 39 , 40 , 41 ]; (ii) decreased symptoms and impact of FM on participants [ 1 , 5 , 15 , 17 , 23 , 33 , 36 , 37 , 41 ]; (iii) lower limb strength [ 1 , 15 , 33 ]. These results are in line with other authors who claim that physical exercise programs are important stimuli with positive influence, attenuating the symptoms of the disease, through changes in the hypothalamic–pituitary–adrenal axis (HPA)—resulting in the release of neurotransmitters due to exercise and controlling and/or reducing localised pain [ 16 , 42 ]. The major findings were the improvement of health-related life quality, pain intensity, stiffness, fatigue, physical function, withdrawals and absence of adverse events [ 17 , 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the studies that were analysed, significant values were found for at least one of the evaluated parameters in all studies: (i) physical fitness tests [ 1 , 23 , 33 , 36 , 37 , 39 , 40 , 41 ]; (ii) decreased symptoms and impact of FM on participants [ 1 , 5 , 15 , 17 , 23 , 33 , 36 , 37 , 41 ]; (iii) lower limb strength [ 1 , 15 , 33 ]. These results are in line with other authors who claim that physical exercise programs are important stimuli with positive influence, attenuating the symptoms of the disease, through changes in the hypothalamic–pituitary–adrenal axis (HPA)—resulting in the release of neurotransmitters due to exercise and controlling and/or reducing localised pain [ 16 , 42 ]. The major findings were the improvement of health-related life quality, pain intensity, stiffness, fatigue, physical function, withdrawals and absence of adverse events [ 17 , 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…Aerobic exercises seem to be fundamental stimuli in exercise programs as they induce adaptations in several systems, namely in the cardiovascular, energetic, neuromuscular and neuroendocrine systems [ 43 ]. The latter allows an increase in serotonin and norepinephrine concentrations, with a consequent improvement in mood and greater physical well-being [ 16 , 47 ]. The norepinephrine and serotonin are involved in the modulation of arousal and mood and have been related to a variety of affective functions as well as associated clinical dysfunctions [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies selected for this review, cortisol levels were determined using diagnostic tests on blood, saliva or urine samples. Several authors have established that morning cortisol levels in serum [ 49 ], saliva [ 50 , 51 ] or hair [ 51 ] are lower in subjects with chronic musculoskeletal pain [ 52 ], FM [ 49 , 50 ] or chronic fatigue syndrome [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…La diferencia entre los individuos con edorexia y el grupo control parece indicar que el ejercicio se puede emplear como una herramienta para conseguir una finalidad como, por ejemplo, compensar la ingesta de alimentos o aliviar el malestar después de comer en exceso y así conseguir un alivio de sus emociones. El uso de actividad física como una técnica para aliviar síntomas no es nuevo, se emplea en diabetes (van Laake-Geelen, Smeets, Quadflieg, Kleijnen, y Verbunt, 2019), fibromialgia (Bonnabesse et al, 2019) e incluso en los trastornos alimentarios (Danielsen, Ro, y Bjornelv, 2018).…”
Section: Discussionunclassified